Struktur Fisik dan Struktur Batin Pada Puisi Tuhan, Aku Cinta Padamu Karya WS Rendra - Muntazir, Muntazir (JURNAL PESONA, 2017)
AbstractÂ Poetry is the oldest literary form. It emerges with the presence of man. The study of poetry focused on the physical structure and inner structures of poetry. This study used a descriptive qualitative method. Stylistic analysis approach: (1) systematic analysis of linguistic system of literary works, and continued to the interpretation of literary characteristics, interpretation directed to the total meaning; (2) studying a number of distinctive features that distinguish one system from another. The poem "Tuhan"Aku Cinta Padamuâ sounds / a / who dominates, the atmosphere of longing, emotion, surrender, willingness and peace. Repetition of rhymes in words in poems, visual images, movements, feelings, metaphors, and repositories. The theme of God, the mandate for self-introspection in order to improve themselves for reaching the Godâs willing.Keywords: literary, poetry, stylistic